Implementation of light extraction improvements of GaN-based light-emitting diodes with specific textured sidewalls. (May 2018) - Chen, Chun-Yen; Chen, Wei-Cheng; Chang, Ching-Hong; Lee, Yu-Lin; Liu, Wen-Chau
Highlights: Textured sidewall structures were achieved by lithography and ICP approaches. Specific sidewall structures were comprehensively fabricated and studied. Optical properties were improved with 45° and convex sidewalls structures. The negligible degradation in electrical properties was found. Abstract: Textured-sidewall GaN-based light-emitting diodes (LEDs) with various sidewall angles (15–90°) and convex or concave sidewalls prepared using an inductively-coupled-plasma approach are comprehensively fabricated and studied. The device with 45° sidewalls (Device F) and that with convex sidewalls (Device B) show significant improvements in optical properties. Experiments show that, at an injection current of 350 mA, the light output power, external quantum efficiency, wall-plug efficiency, and luminous flux of Device F (Device B) are greatly improved by 18.3% (18.2%), 18.2% (18.2%), 17.3% (19.8%), and 16.6% (18.4%), respectively, compared to those of a conventional LED with flat sidewalls. In addition, negligible degradation in electrical properties is found. The enhanced optical performance is mainly attributed to increased light extraction in the horizontal direction due to a significant reduction in total internal reflection at the textured sidewalls. Therefore, the reported specific textured-sidewall structures (Devices B and F) are promising for high-power GaN-based LED applications.